Potensi dan Kendala Kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan di Kabupaten Demak - Rokhmah, Meirina (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Perlindungan Lahan Pertanian Pangan Berkelanjutan (PLP2B â€ Sustainable Farm Land Protection) is a government policy aimed to prevent farm land conversion. It has been implemented among others in Demak Regency, which is one of the regionâ€™s main food source. The study identified the potential and challenges of the implementation of the policy through the method of superimpose between the planned map and the actual land use conversion, supported by land conversion data from the Land Office and interview with selected sources. The study showed that land conversion is still occurring and that there are mismatches between the planned map and the actual condition. Interviews suggested that there still vast measure of farm land available still for improvement into sustainable farm lands. Challenges emerge from the high demand for housing areas, illegal land conversion and lack of policy socialization to thecommunity.